Türkiye’de En Çok Tercih Edilen Vakıf Üniversitelerinin Görsel Kimlik Tasarımlarının Analizi - Sungur, Suat (The Turkish Online Journal of Design Art and Communication, 2012)
Today, the need for products and services provided by the institutions and the agent has ceased to function physically. This has added a different dimension institutions of different items from other competitors, marketing strategies and visual identities of the identity of the product and service. In this competitive environment, the differences between corporate identity and visual identity, design elements that are effective in the process, memorable and distinctive features of the visual identity of the institution have become important elements to consider in the design stage. In a highly competitive market this study aims to demonstrate the importance of the differentiation of visual identity and its returns using examples from 2011 according to OSYM data in the list of the most preferred top three foundation universities and analyze the visual identity designs of these universities. As a result of the study, the idea of creating a memorable visual identity based on the characteristics of these institutions and their own distinctive visual identity differences in this competition has been emphasized.
Keywords: Identity; Visual Identity; Corporate Identity; Foundation Universities; Kimlik; Görsel Kimlik; Kurumsal Kimlik; Vakıf Üniversiteleri